FOXO3A Expression in Upper Tract Urothelial Carcinoma - Zhang, Guoyao; Shi, Wanping; Jia, Enzhao; Zhang, Lei; Han, Yongsheng; Rodriguez, Ronald; Ma, Tianjiang (Frontiers in Oncology, 2021)
Background Epidemiological studies have reported various results regarding whether FOXO3A is related to various carcinomas. However, the prognostic significance of FOXO3A in upper tract urothelial carcinoma (UTUC) remains unclear. The purpose of this study was to validate the correlation between FOXO3A expression and oncological outcomes in UTUC. Methods The expression levels of FOXO3A in 107 UTUC patients were examined by immunohistochemistry (IHC). We examined the prognostic role of FOXO3A by using the Cox proportional hazard model. Results The results indicated that FOXO3A expression was notably decreased in UTUC tissue compared with control tissue. Decreased expression of FOXO3A was also related to advanced pathologic stage (P = 0.026), lymph node metastasis (P = 0.040), lymphovascular invasion (P < 0.001), and adjuvant therapy (P = 0.048). In addition, UTUC patients with low FOXO3A expression had a significantly shorter survival time, including both overall survival (OS) [hazard ratio (HR) 2.382, P = 0.004] and recurrence-free survival (RFS) (HR 2.385, P = 0.004), than those with high expression. Multivariate analyses showed that FOXO3A was a significant predictor for OS (HR 2.145, P = 0.014) and RFS (HR 2.227, P = 0.010) in UTUC patients. Conclusion Our results indicate that FOXO3A may be involved in the recurrence of UTUC and that it has certain clinical value in the therapeutic targeting and prognostic evaluation of UTUC.